E-EVALUATION OF ENGINEERING STUDIES: THEORETICAL OVERVIEW - Aļeksejeva, Anastasija; Zaščerinskis, Mihails; Zaščerinska, Jeļena; Andreeva, Natalia; Melnikova, Julija (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The paradigm shift from input to output based engineering education, on the one hand, and digitalization of engineering education, on the other hand, have influenced the enhancement of such area of engineering studies as e-evaluation. However, e-evaluation of engineering studies has attracted little attention. The aim of the contribution is to analyze theoretical literature on e-evaluation of engineering studies underpinning elaboration of a research question on use of information technologies such as multimedia technologies, information systems, etc for e-evaluation of engineering studies. The meaning of the key concepts of assessment, evaluation and e-evaluation is studied. Moreover, the study shows how the steps of the process are related: theoretical overview of e-evaluation of engineering studies → elaboration of a research question on use of information technologies for e-evaluation of engineering studies → conclusions. The novelty of the present contribution is formulated in the research question on use of information technologies for e-evaluation of engineering studies. Directions of further research are proposed.